2020
DOI: 10.1039/d0sc00031k
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-free C(sp3)–H/C(sp3)–H dehydrogenative coupling of saturated heterocycles with N-benzyl imines

Abstract: A unique transition-metal-free C(sp3)–H/C(sp3)–H dehydrocoupling of N-benzylimines with saturated heterocycles is presented using 2-azaallyl anions as super electron donors to initiate the generation of hydrogen atom abstracting aryl radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…The latter adds to the in situ formed iminium salt B to afford after reduction by Ti(III) species 1,2-aminoalcohol derivatives 168a-c. More recently, Li, Zhang, Yang, Walsh and co-workers developed transition metal-free dehydrogenative crosscoupling of N-benzyl amines and saturated heterocycles (Scheme 43). 91 They have shown that 2-azaallyl anion A, generated by deprotonation of N-benzyl amines, can undergo SET to aryl iodide to form aryl radical and persistent 2-azaallyl radical B. Sterically protected sacrificial aryl radical undergoes intermolecular HAT at activated C(sp 3 )-H sites to form stabilized nucleophilic radical C, which recombines with persistent 2azaallylradical B to deliver the products 174a-d.…”
Section: Intermolecular Hatmentioning
confidence: 99%
“…The latter adds to the in situ formed iminium salt B to afford after reduction by Ti(III) species 1,2-aminoalcohol derivatives 168a-c. More recently, Li, Zhang, Yang, Walsh and co-workers developed transition metal-free dehydrogenative crosscoupling of N-benzyl amines and saturated heterocycles (Scheme 43). 91 They have shown that 2-azaallyl anion A, generated by deprotonation of N-benzyl amines, can undergo SET to aryl iodide to form aryl radical and persistent 2-azaallyl radical B. Sterically protected sacrificial aryl radical undergoes intermolecular HAT at activated C(sp 3 )-H sites to form stabilized nucleophilic radical C, which recombines with persistent 2azaallylradical B to deliver the products 174a-d.…”
Section: Intermolecular Hatmentioning
confidence: 99%
“…For the sink tie line lying below, between, and above the coupled sink and source, its HUA can be determined by Eqs. (2), (3), and (4), respectively . true right1 left Δ Fnormalu = Fnormalu,0 - Fnormalu = right1 left - Hi +(Δ FS Kq -Δ FS Rp ) cnormalS normalRi -Δ( FS Kq cS Kq )+Δ( FS Rp cS Rp ) cnormalu - cnormalS normalRi trueΔ Fnormalu =- Hi +Δ FnormalS normalKnormalq cnormalS normalRi -Δ( FS Kq cS Kq ) cnormalu - cnormalS normalRi …”
Section: Introductionmentioning
confidence: 99%
“…Ng et al proposed the pinch‐based automated approach to target the minimum utility consumption of the property and concentration‐based conservation networks with regeneration/purification reuse. Liu et al developed a systematic method to identify the quantitative relationships among the hydrogen utility consumption and the purification feed and purified product , the limiting and optimal purification feed flow rate , the limiting and optimal purification feed and purified product purity , hydrogen recovery as well as optimization of flow rate and purity of the purification feed simultaneously . Zhang et al proposed the quality triangle rules and developed a graphic method for analyzing hydrogen utility consumption of the hydrogen network with purification.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations